PEMBAHARUAN PENDIDIKAN ISLAM DI BANTEN AWAL ABAD XX: (Studi atas Mathla’ul Anwar dan Al-Khairiyah)∗ - Maftuh, Maftuh (Analisis: Jurnal Studi Keislaman, 2011)
Banten is unique compared to other places in Indonesia. It has a long tradition  of obedience  to Islam, and history of struggle  against  the Dutch  colonialism.  When  the  spirit  wind  of reform  hits  almost  all regions  of the archipelago  in early twentieth  century,  Banten  came through it in the 1920’s. This article attempts to trace the history of Islamic education reform in Banten. Then, by the use of comparative method, this paper has provided a better explanation of the first Islamic educational organization in Banten to apply modern educational system in the organization of education. In this context, the author examines two educational institutions that existed in Banten, namely Mathla’ul Anwar and Al-Khairiyyah  with the focus on aspects of reforms they suggested  to  do.  These  two  institutions  of  Islamic  education  are pioneers of Islamic education reform which succeeded in transforming the traditional  Islamic educational  institutions  of pesantren  into the form of madrasah schools, and later contribute to the birth of some leaders of Islamic education in all regions of Banten. Study of these two institutions is inevitably relevant and significant to understanding the phenomenon of Islamic education in Banten.